Cardiopulmonary support in patients undergoing catheter ablation of poorly tolerated ventricular arrhythmias and electrical storm. (4th June 2019) - Di Monaco, Antonio; Quadrini, Federico; Troisi, Federica; Vitulano, Nicola; Caruso, Rosa; Duni, Nicola; Cecere, Giacomo; Guida, Piero; Langialonga, Tommaso; Grimaldi, Massimo
Abstract: Introduction: Catheter ablation is an important treatment option for sustained ventricular arrhythmias (VA) that are refractory to pharmacological treatment; however, patients with fast VA or electrical storm (ES) are at risk for cardiogenic shock. We report our experience using cardiopulmonary support with extracorporeal membrane oxygenation (ECMO) during catheter ablation of VA. Methods: Nineteen patients (mean age, 62 ± 10 years; 84% male) were referred to our center for CA of ES between January 2017 and April 2018. ES was defined as the occurrence of ≥3 ventricular tachycardia or ventricular fibrillation episodes requiring electrical cardioversion or defibrillation in a 24‐hour period. ECMO support was implemented for all patients. Results: CA of ES was completed in all patients. Activation mapping was performed for all VTs and substrate modification was performed by targeting sites identified by late/fragmented abnormal potentials. VTs were not inducible after ablation in 16 of 19 patients (84%). With regard to procedural complications, two patients underwent percutaneous angioplasty with stenting for a femoral artery dissection and one patient was treated for a dislodged ECMO arterial cannula and subsequent hemorrhagic shock. After a median follow‐up of 10 months, three patients died from refractory heart failure and one patient died as a result of ES. Overall, the procedural success rate was 68% and the Kaplan‐Meier mortality rate was 21%. Conclusions: ECMO support may be used for ablation procedures in patients with ES.